The influence student placement experience can have on the employment choices of graduates: A paediatric nursing context. Issue 1 (January 2016) - Boyd-Turner, Danni; Bell, Elaine; Russell, Alison
Abstract: This paper explores how the student placement experience may influence employment choices in the context of paediatric nursing. A qualitative research methodology was used. Data was collected using semi structured interviews at a tertiary teaching hospital. The sample group comprised of six newly qualified nurses who had completed their Bachelor of Nursing less than 12 months before the interview. They had completed at least one clinical placement at the site of data collection in their 2nd or 3rd year of undergraduate nursing studies. The main themes contributing to the student nurse experience within the context of paediatric nursing included the wish to work with children, a job being available, support during clinical placements and assistance with future career planning while on placement. The support experienced by student nurses during their clinical placement was seen to have a very positive influence on their future employment choices. Group de-briefing to support mutual understanding and sharing was seen to be a highly positive aspect of a clinical placement. Also how students were treated by clinical staff was a key factor that influenced future employment choices. Highlights: Focuses on the specialist context of paediatric nursing. Highlights what nursing students found to be positive aspects of the clinical placement. Discusses what nursing students found to be negative aspects of the clinical placement. Illuminates the impact the student facilitator may have on future employment choices. Explores how future employment choices are made by nursing graduates.